2010
DOI: 10.1007/s11947-010-0349-x
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide Mitigation in Potato Chips by Using NaCl

Abstract: In April 2002, Swedish researchers shocked the world when they presented preliminary findings on the presence of acrylamide in fried and baked foods, most notably potato chips and French fries, at levels of 30-2,300 ppb. The objective of this research was to study the effect of immersing potato slices in a NaCl solution over the acrylamide formation in the resultant potato chips. Potato slices (Verdi variety, diameter 40 mm, width 2.0 mm) were fried at 170°C for 5 min (final moisture content of ∼2.0%). Prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 19 publications
1
25
0
1
Order By: Relevance
“…The color is affected by the type of blanching treatment used; Pedreschi et al (2009) observed that a 3% NaCl solution reduces non-enzymatic browning by leaching the reducing sugars and reducing the acrylamide content. According to the observations from the sensory analysis participants, the color of the french fries varied as follows: NaCl produced a more golden color, while the control samples were more brownish, and CaCl 2 produced a paler but uniform coloration.…”
Section: Resultsmentioning
confidence: 99%
“…The color is affected by the type of blanching treatment used; Pedreschi et al (2009) observed that a 3% NaCl solution reduces non-enzymatic browning by leaching the reducing sugars and reducing the acrylamide content. According to the observations from the sensory analysis participants, the color of the french fries varied as follows: NaCl produced a more golden color, while the control samples were more brownish, and CaCl 2 produced a paler but uniform coloration.…”
Section: Resultsmentioning
confidence: 99%
“…Several of these additives have inhibition effects, such as organic acids [16,17], chlorates [17,18,19], phenolic compounds [20,21], and plant extract [22,23]. In contrast, several of these additives have promoting effects, such as sucrose [24] and butylated hydroxytoluene [25].…”
Section: Introductionmentioning
confidence: 99%
“…Formation of acrylamide, a probable human carcinogen and a neurotoxicant in heated carbohydrate‐rich foodstuffs, has raised recent public concern. Therefore, reduction of acrylamide content has been the subject of great interest to many researchers . It is now widely accepted that acrylamide is formed during the Maillard reaction between the amino acid asparagine and reducing sugars at temperatures above 120 °C …”
Section: Introductionmentioning
confidence: 99%